Nitrogen loads to New Zealand aquatic receiving environments: comparison with regulatory criteria. Issue 3 (2nd July 2020) - Snelder, Ton H.; Whitehead, Amy L.; Fraser, Caroline; Larned, Scott T.; Schallenberg, Marc
ABSTRACT: There is concern about the deteriorating nutrient status of aquatic receiving environments in New Zealand. We estimated the amount by which current nitrogen (N) concentrations and loads exceed criteria in rivers, lakes and estuaries nationally. Criteria corresponded to national 'bottom-line' (i.e. minimal) environmental objectives set by government policy. Three metrics were evaluated: (1) degree of compliance describes the current TN loads in receiving environments relative to criteria; (2) catchment N status describes the acceptability of catchment N loads compared to criteria; and (3) excess load indicates the amount by which the N load exceeds the maximum allowable load (kg yr −1 ). Non-compliance with N criteria was broadly distributed nationally particularly in low-elevation catchments. Catchments with unacceptable N status constituted at least 31% of New Zealand's land area, which corresponds to at least 43% of the country's agricultural land. The national excess load was estimated to be at least 19.1 Gg yr −1 . We are 97.5% confident that estimated excess loads exceed zero for nine of 15 regions and for the nation as a whole. The analyses provide a strategic assessment of where reductions in N emissions are required to achieve the minimal national objectives.